The Influence of Production Costs and Operational Costs on Profitability in Manufacturing Companies - Asriany, Asriany; Budiandriani, Budiandriani; Imanuddin, Imanuddin (Journal of Economic Education, 2024)
This research aims to determine the effect of operational costs on profitability in manufacturing companies listed on the Indonesia Stock Exchange. This research uses quantitative methods and the source data used is secondary data in the form of financial reports. The population in this study were 30 manufacturing companies operating in the industrial and chemical sectors on the Indonesia Stock Exchange for the period 2016 - 2020. The sampling technique used purposive sampling technique with a sampling method based on certain criteria. This research uses E-Views data processing with multiple linear regression estimation. The research results show that production costs have an effect on profitability while operational costs have no effect on profitability